ENVIRONMENTAL IMPACT ASSESSMENT, PERSONAL HYGIENE, AND OCCUPATIONAL HISTORY ON THE INCIDENCE OF DERMATITIS - Marniati Marniati; Enda Silvia Putri; Sufyan Anwar; Itza Muliyani; Susy Sriwahyuni; Khairunnas Khairunnas (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2021)
The environment is a very influential factor in the incidence of dermatitis. Dermatitis is a skin disease that is acute, sub-acute/ or chronic caused by inflammation of the skin that occurs due to exogenous and endogenous factors. The problem in this study is the high prevalence of dermatitis in the community, reaching 623 cases. The purpose of this study is to analyze the analysis of the impact of environmental studies, personal hygiene, and work history on the incidence of dermatitis in the community in the Darul prosperous sub-district, Nagan Raya district. This research method is an analytic design with a Cross-sectional design. This research was carried out in December 2020 which became the population of people with Dermatitis with a sample of 86 respondents. This study was analyzed using univariate and bivariate, then tested by Chi-Square test. The results of the study after being tested stated that there was an influence of environment, personal hygiene, and work history on the incidence of dermatitis as evidenced by the P.value 0.05. The conclusion after analyzing the effect of the model on the impact of work history, personal hygiene, and the environment there is an influence on the incidence of dermatitis. Among all these variables the most powerful influence is the environmental variable. Suggestions to the Puskesmas to further improve policies in dealing with the incidence of dermatitis by approaching and empowering the community so that a dermatitis-free society is achieved.